Kolaborasi Antar Perangkat Daerah di Pemerintahan Daerah Kabupaten Gunungkidul - Juniyanto, Juniyanto - (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
The purpose of this study was to find indicators in the dimensions of governance, administration, autonomy, mutuality and norms to measure the collaboration of regional apparatus and calculate the total score and each score in the dimensions of governance, administration, autonomy, mutuality and norms of collaboration of regional apparatus in the Regency Regional Government. South Mountain. The result of the research is that there are 26 indicators that represent a multidimensional collaboration scale that has a valid measure based on theoretical and statistical data from the five dimensions. The conclusions are some inputs for the Government in Gunungkidul Regency, namely (a) increasing informal relations, (b) increasing leadership in carrying out the roles and responsibilities of each regional apparatus in collaboration, (c) simplify the organizational structure to maximize the division of roles and authority; (d) increasing transparency in building commitment to sustainable collaboration; and (e) increasing self-capacity and building more trust among regional officials.